RIQUEZA E EXCLUSÃO SOCIAL: O PARADOXO DOS ROYALTIES DO PETRÓLEO - Pizzol, Rosa Amélia (2008)
The oil royalties are an expressive found resources to many states and brazilian cities located in oil production regions, mainly after the Oil Law (number 9.478/97). Ahead of this fact and considering the limited capacity to supply of the oil, one goal in this work is investigate if these resources are reverting in the promotion of the improvement of the quality of life of the population and in the diversification of the local productive bases, aiming at the creation of new alternatives of sustainable development for these cities. It's inquired if the incomes proceeding from the oil, in the form of royalties, are being onslaughts in projects in order to prevent the economic decline, the economic sustentability for the region in public politics that they aim at to minimize the processes of social and ambient impoverishment.